2018
DOI: 10.1017/jfm.2018.348
|View full text |Cite
|
Sign up to set email alerts
|

The kinematics of bidisperse granular roll waves

Abstract: Small perturbations to a steady uniform granular chute flow can grow as the material moves downslope and develop into a series of surface waves that travel faster than the bulk flow. This roll wave instability has important implications for the mitigation of hazards due to geophysical mass flows, such as snow avalanches, debris flows and landslides, because the resulting waves tend to merge and become much deeper and more destructive than the uniform flow from which they form. Natural flows are usually highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 61 publications
4
28
0
2
Order By: Relevance
“…Interestingly, simulations with ξ = 1 show the tendencies to produce wave-like instabilities in situations without entrainment. This behaviour can be explained by the rheological model and is commonly observed [50]. We find that the classic Voellmy model does not tend to produce these instabilities.…”
Section: A)supporting
confidence: 68%
“…Interestingly, simulations with ξ = 1 show the tendencies to produce wave-like instabilities in situations without entrainment. This behaviour can be explained by the rheological model and is commonly observed [50]. We find that the classic Voellmy model does not tend to produce these instabilities.…”
Section: A)supporting
confidence: 68%
“…Numerical solutions are calculated using a high-resolution semi-discrete nonoscillatory central (NOC) scheme for convection-diffusion equations (Kurganov & Tadmor 2000). This method has proved its ability to solve similar systems of conservation laws for erosion-deposition waves (Edwards & Gray 2015;Edwards et al 2017), segregation-induced finger formation (Baker et al 2016b) and bi-disperse roll waves (Viroulet et al 2018). The equations are solved in conservative form, where U = (h, hū, hv) T is the vector of conserved fields, with U x and U y being the derivatives of U with respect to x and y, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that the depth-averaged viscous terms (Gray & Edwards 2014;Baker, Barker & Gray 2016a), which are crucial for the formation of leveed channels on non-erodible slopes (Rocha, Johnson & Gray 2019), can be neglected here because the retrogressive failures are planar. It is, however, anticipated that viscous terms could well be important for non-planar retrogressive waves, where cross-slope gradients in the velocity will develop naturally, or, for the correct cutoff frequency and coarsening dynamics of roll waves and erosion-deposition waves that may form downstream of the failure front (Gray & Edwards 2014;Edwards & Gray 2015;Viroulet et al 2018). Gray & Edwards (2014) showed that, to leading order in the aspect ratio, both the inviscid avalanche equations (3.1)-(3.2) and the dynamic friction law of Pouliquen & Forterre (2002) emerge naturally from depth averaging the µ(I)-rheology for granular flows (GDR-MiDi 2004;Jop et al 2006).…”
Section: Governing Equationsmentioning
confidence: 99%